2009
DOI: 10.1002/poc.1551
|View full text |Cite
|
Sign up to set email alerts
|

Influence of substitution of oxygen by sulfur on maltol properties

Abstract: Replacing oxygen by sulfur in a maltol molecule generates a family of new very interesting ligands: thiohydroxypyrones. In this work, theoretical calculations have been performed for all possible maltol derivatives created by consecutive substitutions of oxygen atoms by sulfur. The study is focused on molecular properties of thioligands, which are important for the formation of their metal complexes, and potentially useful in medicinal and environmental chemistry. Energetic, tautomeric, aromatic, and charge di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 40 publications
1
15
0
Order By: Relevance
“…A range of vanadium-sulfur complexes and their chemistries have demonstrated that vanadium-sulfur complexes have interest as models for nitrogenase chemistry,2 as the vanadium binding proteins,3,4 as anti-amoebic agents,57 as anti-diabetic agents,8 and as catalysts 9,10. The literature provides many examples that rapid reduction of vanadium(V) compounds takes place in the presence of biological thiols such as glutathione, cysteine, 2-mercaptoethanol and dithiothreitol (DTT) under physiological conditions 1117.…”
Section: Introductionmentioning
confidence: 99%
“…A range of vanadium-sulfur complexes and their chemistries have demonstrated that vanadium-sulfur complexes have interest as models for nitrogenase chemistry,2 as the vanadium binding proteins,3,4 as anti-amoebic agents,57 as anti-diabetic agents,8 and as catalysts 9,10. The literature provides many examples that rapid reduction of vanadium(V) compounds takes place in the presence of biological thiols such as glutathione, cysteine, 2-mercaptoethanol and dithiothreitol (DTT) under physiological conditions 1117.…”
Section: Introductionmentioning
confidence: 99%
“…The results of these calculations are collected in Table . The examination of these data clearly shows that the previously established order of aromaticity for maltol, other hydroxypyrones and maltol thio derivatives also remains in the present seleno compounds. The aromaticity order of hydroxypyrones and their derivatives starts with the anionic form that is non‐aromatic or sometimes slightly anti‐aromatic (depending on the aromaticity index and the position(s) and number(s) of oxygen atoms that are replaced by selenium).…”
Section: Resultsmentioning
confidence: 99%
“…However, unlike B3LYP, B1LYP has only one parameter that is additionally not fitted, but it is rooted in the theory. The B1LYP functional was used in our previous investigation on thiohydroxypyrones . Thus, the results collected in the previous calculations and in this study can be compared.…”
Section: Computational Detailsmentioning
confidence: 99%
See 2 more Smart Citations